A polynomial Ansatz for norm-conserving pseudopotentials. (14th June 2018) - Kiffner, Martin; Jaksch, Dieter; Ceresoli, Davide
Abstract: We show that efficient norm-conserving pseudopotentials for electronic structure calculations can be obtained from a polynomial Ansatz for the potential. Our pseudopotential is a polynomial of degree ten in the radial variable and fulfils the same smoothness conditions imposed by the Troullier–Martins method (TM) (1991 Phys. Rev . B43 1993) where pseudopotentials are represented by a polynomial of degree twenty-two. We compare our method to the TM approach in electronic structure calculations for diamond and iron in the bcc structure and find that the two methods perform equally well in calculations of the total energy. However, first and second derivatives of the total energy with respect to atomic coordinates converge significantly faster with the plane wave cutoff if the standard TM potentials are replaced by the pseudopotentials introduced here.